IODP Expedition 382: Supplementary Tables for "New magnetostratigraphic insights from Iceberg Alley on the rhythms of Antarctic climate during the Plio-Pleistocene" - Reilly, Brendan; Tauxe, Lisa; Brachfeld, Stefanie; Raymo, Maureen; Bailey, Ian; Hemming, Sidney; Weber, Michael; Williams, Trevor; Garcia, Marga; Guitard, Michelle; Martos, Yasmina; Pérez, Lara; et al. (Zenodo, 2020)
Supplementary tables for "New magnetostratigraphic insights from Iceberg Alley on the rhythms of Antarctic climate during the Plio-Pleistocene" Includes stratigraphic data for International Ocean Discovery Program (IODP) Expedition 382 Sites U1536 and U1537. Table Captions: Table S1. Splice table and additional appended cores for Site U1536 used in this study. Table S2. Splice table and additional appended cores for Site U1537 used in this study. Table S3. Correlation table for creation of correlated equivalent depth (ced) scale between Sites U1536 and U1537. Table S4. Uncertainty estimates for Site U1536 natural gamma radiation (NGR) correlation to Site U1537 on mcd depth scale using Undatable (Lougheed & Obrochta, 2019). Table S5. Site U1536 inclination, natural gamma radiation (NGR), gamma ray attenuation (GRA), and b* data used in this study. Table S6. Site U1537 inclination, natural gamma radiation (NGR), gamma ray attenuation (GRA), and b* data used in this study. Table S7. Meters below sea floor (mbsf) depths of magnetic reversals at Site U1536. Reversal ages are those used in this study’s age models (see Methods; Channell et al., 2016; Lisiecki & Raymo, 2005). Table S8. Meters composite depth (mcd) splice depths of magnetic reversals at Site U1536. Reversal ages are those used in this study’s age models (see Methods; Channell et al., 2016; Lisiecki & Raymo, 2005). Table S9. Meters below sea floor (mbsf) depths of magnetic reversals at Site U1537. Reversal ages are those used in this study’s age models (see Methods; Channell et al., 2016; Lisiecki & Raymo, 2005). Table S10. Meters composite depth (mcd) splice depths of magnetic reversals at Site U1537. Reversal ages are those used in this study’s age models (see Methods; Channell et al., 2016; Lisiecki & Raymo, 2005). Table S11. Magnetostratigraphic age model for Site U1536 generated with Undatable (Lougheed & Obrochta, 2019). Table S12. Magnetostratigraphic age model for Site U1537 generated with Undatable (Lougheed & Obrochta, 2019). Table S13. Dove Bain data stacks used in this study. Table S14. Stratigraphic summary of magnetic reversals discussed in this study. U1308 ages from Channell et al., 2016. In relation to benthic δ 18 O, warm intervals are intervals with more positive values. In relation to Dove Basin facies, warm intervals are intervals with high higher b*, lower NGR, and lower GRA.